Student Acceptance of Mobile Videos in Online Learning: An Application of the Technology Readiness and Acceptance Model - Nghi Nguyen; Le Thi Dieu Hien (Journal of Economic Education and Entrepreneurship Studies, 2025)
This study examines student acceptance of mobile videos in online learning by applying the Technology Readiness and Acceptance Model (TRAM). The research investigates the relationships between technological readiness, perceived ease of use, perceived usefulness, and students’ intention to use mobile video-based learning tools. A quantitative research design was employed, with data collected from university students using a quota sampling technique. Structural Equation Modeling (SEM) was applied to test the proposed research model and examine both direct and indirect relationships among the constructs. The findings indicate that technology readiness has a significant positive effect on perceived ease of use, perceived usefulness, and students’ intention to use mobile videos in online learning. Furthermore, perceived ease of use and perceived usefulness are found to significantly influence students’ behavioral intention to adopt mobile video-based learning. These results highlight the critical role of individual readiness toward technology in shaping students’ acceptance of digital learning media. The study contributes to the literature on adoption of educational technology by confirming that technology readiness is a key antecedent of mobile learning acceptance. Practical implications suggest that educational institutions should strengthen students’ technological readiness to enhance the effectiveness and sustainability of mobile video-based online learning.